Vulnerability of Medicinal Plants Used in the Treatment of Sexual Weaknesses among the Ngengele of Tchambi, Maniema (DR Congo) - USSENI NASIBU, Hilaire; KAPOLI OMBA, Dan; YAKAYENGO TOKO, Augustin; YUMA MADJALIWA, Pierre; LOMBA BOSOMBO, Christophe; NSHIMBA SEYA, Hippolyte (European Journal of Science, Innovation and Technology, 2025)
The use of medicinal plants to treat sexual weaknesses remains common among the Ngengele communities of Tchambi (Maniema Province, DR Congo). However, the intensive exploitation of roots, bark, and other organs threatens the survival of many species. This study aimed to inventory the locally used aphrodisiac plants and to assess their degree of vulnerability. Ethnobotanical surveys were conducted with 80 traditional healers (32 women and 48 men) across ten villages. A vulnerability index (IVi), based on nine ecological and ethnobotanical parameters, was calculated. A total of 26 species belonging to 15 families were recorded. Among them, 65% were classified as highly vulnerable, including Millettia elskensii (IVi = 2.9), and 35% as moderately vulnerable. The dominant use of bark and roots (59% of reported uses) places significant pressure on natural regeneration. These findings confirm that current management practices are unsustainable and highlight the urgent need for awareness raising, domestication, and participatory conservation strategies.